Activation of neutrophils in pathological conditions of ischemia and cardiovascular consequences, roles of nitric oxide /no/ and pharmacological ways of regulation - Rutowski Jan Antoni (Актуальні проблеми транспортної медицини, 2013)
Major role in the pathogenesis of the changes development in the heart tissue due to anoxia during myocardial infarction play activated polymorphonuclear leukocytes. Under conditions of hypoxia activated neutrophils are generating oxygen free radicals and releasing the contents of their granules with a number of lysosomal enzymes. There are very interesting to have different possibilities of pharmacological regulation of this kind of pathology of a high activated neutrophils. For example, stimulation of adenylate cyclase by prostaglandin E2 (PGE2) in neutrophils can leads to an increase of intracellular cAMP levels in neutrophils, and then to reduction of leukotrienes formation and to reduction of the in flammatory processes degree. The use of compounds in pharmacotherapy, which are inhibitors of the enzyme phosphodiesterase (cAMP degrading enzyme) can also enhance the effect of elevated concentration of cAMP and thus leads to suppression in the activation processes of neutrophils and also platelets. The compounds, which can inhibit the process formation from arachidonic acid (AA) some active metabolites by activated neutrophils, are also important during heart ischemia. Moreover, we have known a synergistic effect between stimulators of cAMP and cGMP (by EDRF/NO) in the white blood cells and platelets. Endogenous EDRF/NO is synthesized from the aminoacid Larginine by the enzyme NOsyntase, mainly in the vascular endothelium as well as in other cells. NO is constitutively secreted by endothelial cells but its production is modulated by a number of exogenous chemical and physical stimuli, whereas the other known mediators (PGI2, Endothelin-1 and PAF) are synthesized primarily in response to changes in the external environment. Both endogenous and exogenous NO (liberated from NO-donors) may bind to the heme enzyme guanylate cyclase. This effect is stimulated by guanylate cyclase and then followed by the increase of the cGMP production in the cells. Reduction of endogenous NO formation in the absence of substitution, lead to a number of causes pathological changes in a front of acceleration of aterothrombosis process, higher activation of platelets and more opportunities for their adhesion and aggregation particularly in ischemic and hypoxic conditions, the shrinkage of blood vessels, reducing the blood flow through the coronary arteries, and in the case of beginning myocardial infarction to extend the zone of ischemia and necrosis of hemodynamic consequences. Reduced endogenous production of NO and thus the deficiency occurs in conditions of excessive production and release of active vasoconstriction compounds (leukotrienes, in front of leukotriene B4 as well as thromboxane A2 and endothelin 1) deepens further reduced vascular flow, leading to coronary artery spasm. Pharmacological ability to regulate the biosynthesis of endogenous NO with elevation of NO level in cells in various stages of pathological condition because of heart ischemia can be also conducted by NO-donors a compounds that can release from their structure egzogenous nitricoxide (NO). Moreover, negative effects of oxygen free radicals overgeneration by activated polynuclear granulocytes during ischemia and hypoxia condition can be regulated by freeradicals scavengers. The knowledge of different mechanisms with pathologic consequences activation of neutrophils during aseptic inflammation caused by ischemia and hypoxia as well as these processes possibility of pharmacological regulation are necessary to proper introduce and effective conduction of optimal pharmacotherapy of cardiovascular pa; thology caused by ischemia and hypoxia. Показаны механизмы патологии,
роль и негативные последствия повышенной генерации свободных радикалов
кислорода активированными полиморфоядерными гранулоцитами при ишеми;
ческом и гипоксичном состояниях, изменения, вызванные высвобождением ряда
лизосомальных ферментов из;за асептического воспаления, вызванного ишемией и гипоксией. Рассмотрены влияние и
механизм действия оксида азота на фоне
ряда патологических состояний сердечно;сосудистой системы. Показано механізми патології, роль
і негативні наслідки підвищеної генерації
вільних радикалів кисню активованими
поліморфоядернимі гранулоцитами при
ішемічному і гипоксічному станах, зміни,
викликані вивільненням ряду лізосомальних ферментів через асептичного запалення при ішемії та гіпоксією. Розглянуто
вплив і механізм дії оксиду азоту на тлі
низки патологічних станів серцево-судинної системи.